Social Desirability, defensiveness and self-report psychiatric inventory scores. - Parkes, K (1980)
The effects of social desirability and defensiveness on scores on 2 self-report psychiatric inventories, the General Health Questionnaire (GHQ) and the Middlesex Hospital Questionnaire (MHQ) were investigated in a female subject group assessed for research purposes in an occupational setting. It was found that defensiveness did not affect the reporting of somatic symptoms, but it significantly affected the reporting of all psychological distress. The effect of social desirability was more specific, only the GHQ social dysfunction subscale showing a significant correlation, an effect attributable to the influence of the setting in which the data were obtained.